Immunotherapy for Triple-Negative Breast Cancer - Yifeng Cao; Chuyang Chen; Yi Tao; Weifeng Lin; Ping Wang (Pharmaceutics, 2021)
Triple-negative breast cancer (TNBC) is characterized by extensive tumor heterogeneity at both the pathologic and molecular levels, particularly accelerated aggressiveness, and terrible metastasis. It is responsible for the increased mortality of breast cancer patients. Due to the negative expression of estrogen receptors, progesterone receptors, and human epidermal growth factor receptor 2, the progress of targeted therapy has been hindered. Higher immune response in TNBCs than for other breast cancer types makes immunotherapy suitable for TNBC therapy. At present, promising treatments in immunotherapy of TNBC include immune checkpoints (ICs) blockade therapy, adoptive T-cell immunotherapy, and tumor vaccine immunotherapy. In addition, nanomedicines exhibit great potential in cancer therapy through the enhanced permeability and retention (EPR) effect. Immunotherapy-involved combination therapy may exert synergistic effects by combining with other treatments, such as traditional chemotherapy and new treatments, including photodynamic therapy (PTT), photodynamic therapy (PDT), and sonodynamic therapy (SDT). This review focuses on introducing the principles and latest development as well as progress in using nanocarriers as drug-delivery systems for the immunotherapy of TNBC.